Salivary duct carcinoma of minor salivary gland: A case report with review of literature - Arshdeep Kaur; Chetan Dev Singh Boparai; Anusha Rangare Lakshman; Gogineni Subhas Babu (Wolters Kluwer Medknow Publications, 2019)
Salivary duct carcinoma (SDC) is a rare, highly aggressive neoplasm representing about 1%-3% of all malignant salivary gland tumors. Approximately, 85% of the cases occur in the parotid gland followed by the submandibular gland and minor salivary gland. Pathomorphologically, these tumors showed great similarities to ductal carcinoma of the female breast, which is why they described this tumor as "SDC." This article highlights a case of rapidly growing swelling in the left mandibular region in a 60-year-old female. As this entity is rare and highly aggressive, an early detection followed by appropriate treatment is very important to improve the survival rate of the patient.